Peningkatan Laju Pertumbuhan dan Kandungan Flavonoid Klon Daun Dewa (Gynura pseudochina (L.) DC) Melalui Periode Pencahayaan - Ghulamahdi, Munif i; Aziz, Sandra A.; Nirwan, (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
Lights are influential to increase plant flavonoids content.  The bioactives is needed as medication for human cancer.  The research objectives were to investigate  the effect of lighting periods on the growth and flavonoid content of Gynura pseudochina clones. A split plot design was used  with lighting periods as the main plots (100% light  (full light) for 4 months; 25% shading for 1 month, full light 3 months; 25% shading for 2 months, full light for 2 months; 25%  shading  for 3 months, full  light  for 1 months; 25%  shading  for 4 months; 50% shading  for 1 month, full light for  3 months; 50%  shading for 2 months, full light for 2 months; 50% shading for 3 months, full light for 1 montht; 50% shading for 4 months) and sub plots were two clones (clone 9 from in vitro culture and clone 7 from shoot cuttings). The results showed that maximum LAI (Leaf Area Index) (2.72), RGR (Relative Growth Rate) (0.062 g/g/day), LAR (Leaf Area Ratio) (168.55 cm2/g) and NAR (Net Assimilation Rate) (0.00093 g/cm2/day) were obtained from plants grown under 50% shading for 4 months, full light for 4 months, 50% shading for 2 months and  full light for 2 months, respectively. The maximum plant biomass  (90.92g) was  produced by  plants  grown  under 50%  shading  for 1 month  and full light  for 3 months, while maximum total flavonoids content (11.92%) was obtained from plants under 50% shading for 3 months  and full  light for 1 month, whereas maximum anthocyanine content from those grown under 50% shading for 1 month and full light for 3 months. Clone 9 produced LAI, LAR, and anthocyanine content higher than clone 7, but RGR, NAR, total biomass, and total flavonoid content was lower than clone 7.   Key words:  Lighting periods, growth, flavonoids, Gynura pseudochina , clones